Community Perspectives on Savings and Internal Lending Communities Program: Insights from Rural Guatemala. - Pablo Lamino (Journal of International Agricultural and Extension Education, 2025)
In rural Guatemala, where poverty, limited access to formal financial institutions, and economic inequality persist, community-based financial models like Savings and Internal Lending Communities (SILCs) offer a promising alternative. SILCs have gained recognition for their potential to empower low-income individuals, especially women, by providing accessible savings mechanisms and small loans managed within the community. Grounded in Social Capital Theory, this qualitative case study explores the perceptions of Savings and Internal Lending Community [SILC] participants in two rural Guatemalan communities, focusing on their experiences, the influence of SILCs on their well-being, and their recommendations for program improvement. Employing focus group interviews, observations, document analysis, and a participatory group activity, the study engaged Field Technicians, women SILC members, and non-participating youth. Findings reveal that participants perceive SILCs as a crucial financial safety net and a more accessible alternative to traditional banking, fostering social cohesion and enhancing livelihoods through access to savings and low-interest loans. However, the study also highlights the critical role of trust, with instances of loan default and withdrawal posing challenges. Participants emphasized the need for accountability mechanisms like collateral to mitigate these risks and strengthen group cohesion. Recommendations for improvement include greater flexibility in participation, enhanced coordination and guidance, and the continuous building of trust through transparent practices to ensure program sustainability and community engagement.
Keywords: rural development; microfinance; Guatemala; financial inclusion